Receptor for advanced glycation endproduct modulators: a new therapeutic target in Alzheimer's disease. (March 2015) - Walker, Douglas; Lue, Lih Fen; Paul, Gaurav; Patel, Amar; Sabbagh, Marwan N
<x xml:space="preserve">Abstract</x> Introduction: Reduction in the deposition of amyloid β (Aβ) has been the primary target for Alzheimer's disease (AD) therapeutics recently, but in clinical trials this approach has generally been unsuccessful. A common feature of AD pathology is a complex inflammatory component that could be a target for treatment. One feature of this inflammation has been the involvement of the receptor for advanced glycation endproducts (RAGE), whose ligands include advanced glycation-endproduct-modified proteins as well as lipids and Aβ, which are found at elevated levels in AD brains. Areas covered: In this article, the authors describe the key features of RAGE and how it could have a role in AD pathogenesis. They also summarize experimental animal and clinical data that demonstrate the therapeutic effect of RAGE inhibition and consider what these findings mean for human disease. Expert opinion: RAGE has multiple ligands, including Aβ, that are increased in AD brains. Inhibiting RAGE-ligand interactions without activating receptor signaling can reduce multiple pathological pathways relevant for AD. Several RAGE inhibitors and modulators are now being tested as therapeutics for AD. Recent Phase II studies have established the good safety and tolerability of TTP448 with some evidence of positive benefit at lower dose. This suggests that further studies are required.